Playful classics classical reception as a creative process - Harrisson, Juliette ca. 20./21. Jh; Lindner, Martin 1977-; Unceta Gómez, Luis ca. 20./21. Jh (Bloomsbury Academic, 2025)
"This is the first book to deal exclusively with ludic interactions with classical antiquity - an understudied research area within classical reception studies - that can shed light on current processes of construction and appropriation of the Greco-Roman world. Classical antiquity has, for many years, been sold as a product and consumed in a wide variety of forms of entertainment. As a result, games, playing and playful experiences are a privileged space for the reception of antiquity"--
Enthält Beiträge der Konferenz "Imagines VII - Playful classics", die am 5. und 6. März 2021 unter Organisation der Universität Göttingen online stattfand
Keywords: Civilization, Classical, in mass media; Civilization, Classical / Study and teaching; Social learning; Games; Civilisation ancienne dans les médias; Civilisation ancienne / Étude et enseignement; Apprentissage social; Konferenzschrift -- 2021